2006
DOI: 10.1007/s00402-006-0256-9
|View full text |Cite
|
Sign up to set email alerts
|

Proximal humeral internal locking system (PHILOS) for the treatment of proximal humeral fractures

Abstract: Our results suggest that PHILOS is an effective system for providing fracture stabilisation to bony union but awareness of potential hardware complications is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 16 publications
4
87
1
3
Order By: Relevance
“…In previous studies focused on LPHP and PHILOS fixation of complex fractures, reported complications included avascular necrosis, loss of reduction, plate breakage, and pseudarthrosis/nonunion [6,10,17]. We observed 79 local complications in 60 of 211 patients during the 1-year followup; 35 intraoperative complications were directly related to the initial surgical procedure.…”
Section: Discussionmentioning
confidence: 71%
“…In previous studies focused on LPHP and PHILOS fixation of complex fractures, reported complications included avascular necrosis, loss of reduction, plate breakage, and pseudarthrosis/nonunion [6,10,17]. We observed 79 local complications in 60 of 211 patients during the 1-year followup; 35 intraoperative complications were directly related to the initial surgical procedure.…”
Section: Discussionmentioning
confidence: 71%
“…Keeping in mind the various possible advantage of proximal humerus locking plate. [1,4,8,14,16,29,32,33,37,38,42] In the present study, the average age was lower because a sizeable number of the patients (8 patients) sustained a high energy trauma in road traffic accident. It is pertinent to mention that younger age group is more likely to be outgoing and exposed to road traffic accident as compared to older age group.…”
Section: Section: Orthopaedicsmentioning
confidence: 52%
“…To achieve this goal, a variety of implants of internal fixation have been employed with variable success.Implants can range from percutaneous k-wiring conventional plates such as T plate , [9,36,39,44] blade plate one third tubular plate43,circlage or tension band wiring using a stainless steel wire, [26,38,24] helix wiring, [35] externalfixator, [28,30] intramedullary nail, [14,20,23,24,25,27,41] locking plate, [1,4,8,14,16,29,32,33,37,38,42] to hemiarthoplasty. [19] The best treatment for displaced proximal humerus fracture remains controversial and the discussion about ideal implant for such cases still continues.…”
Section: Section: Orthopaedicsmentioning
confidence: 99%
“…Inclusion criteria included all patients 18 years of age or older with a displaced fracture or fracture-dislocation of the proximal humerus as defined by previously defined criteria [2,5,8,13,14,25,26]. We excluded patients with preexisting nerve deficits before their current proximal humerus fracture.…”
Section: Methodsmentioning
confidence: 99%